Competitive growth of Sb2Se3 and GeSe2 crystals in pseudobinary (GeSe2)x(Sb2Se3)1-x glass-forming materials - Barták, Jaroslav; Valdes Mitchell, Diego Alejandro; Martinková, Simona; Shánělová, Jana; Košťál, Petr (Elsevier Science BV, 2023)
The present study deals with crystal growth in undercooled melts in the GeSe2-rich region of the (GeSe2)x(Sb2Se3)1-x system. Two different crystalline phases (Sb2Se3 and GeSe2) were identified and directly investigated using infrared microscopy. In the case of GeSe2 crystals, the crystal growth rates depended only on the temperature and did not change with the composition of the system. The competitive growth of Sb2Se3 and GeSe2 was described in terms of current crystal growth theories. To complete the viscosity behavior in (GeSe2)x(Sb2Se3)1-x system, new viscosity data were obtained for the (GeSe2)0.9(Sb2Se3)0.1 composition. The combination of growth and viscosity data provides useful information on crystal growth and enables the pre-diction of crystal growth rates in the (GeSe2)x(Sb2Se3)1-x system over a wide temperature range.
Konkureční růst Sb2Se3 a GeSe2 krystalů v pseudobinárních sklotvorných materiálech (GeSe2)x(Sb2Se3)1-x
Keywords: Chalcogenides; Crystal growth; Viscosity; chalkogenidy; růst krystalů; viskozita